Employing automotive security to improve the security of unmanned aerial vehicles - Han, Kyusuk (Frontiers in Communications and Networks, 2023)
The concern about cyber threats on unmanned aerial vehicles (UAVs) increases as they are becoming more sophisticated and widely used in various areas. Although there have been efforts to improve the security of UAVs, their focus is limited to physical attacks and securing communication, and many areas still remain open issues. While a more comprehensive approach is required to improve overall areas of UAVs, it is a reasonable way to look into the case study from other similar cyber-physical systems (CPS). Thus, we see the architectural similarity between UAVs and automobiles. Automotive security has significant improvement throughout the last decade, as vehicles have begun to have connectivity and autonomy. There have been tons of research and development efforts in various aspects including securing the components, securing communications, securing software updates, and securing the overall management system to provide multi-layered security for the automotive environments, and standardization and regulations are being issued. Due to the similarity, employing ideas from the automotive environments in the UAV environments becomes a reasonable approach. In this paper, we show the automotive security trends and discuss how UAV environments are comparable to automotive environments. We then show how security in automotive is being adapted to the UAV with a case study.